The Interrelatıonshıps Between Orthodontıcs And Perıodontıcs - Sevil Akkaya (Galenos Yayinevi, 1989)
It has been known that orthodontic appliances have been a local etiologic factor contributing to periodontal problems. Properly executed tooth movement should be accompanied by a more favorable periodontal response rather than an adverse reaction. Today guiding the patient's orthodontic therapy with fixed and removable appliances requires a sophisticated knowledge of the periodontium. The purpose of this article is to describe several interrelationships between orthodontics and periodontics and to highlight frequent problem areas.